Quality of life in diabetic subjects with respect to metabolic syndrome: a case control study - V., Mahesh; K., Latha; C., Muninarayana; S., Ravishankar (International Journal Of Community Medicine And Public Health, 2016)
Background: Diabetes is a chronic non-communicable disease, leading to many complications and disability. With co morbidities it leads to a substantial decrease in the patients’ quality of life (QoL). In diabetics, psychosocial factors such as depression are stronger predictors of medical outcomes such as hospitalization and death than are physical and metabolic factors such as presence of complications, body mass index, or HbA1c level. Hence this study was conducted with the objectives to correlate the quality of life (QoL) domains with metabolic syndrome parameters among diabetic patients. Methods: Hospital based case control study was done for a period of 3 months among 180 diabetics and non-diabetics in a rural tertiary care centre. Information on socio- demographic profile, diabetic history was collected using a pretested and structured questionnaire. Quality of life was assessed by WHOQOL-BREF. Statistical analysis was carried out by using SPSS 22 Version. Chi-square and independent t-test was the statistical test. Results: Majority of subjects in both groups were females, 56.7% and 54.4% in cases and controls respectively. Mean age of cases and control was 57.9±11.7 years and 57.4±11.2 years respectively. Significant association between diabetes and metabolic syndrome was observed. Quality of life was significantly low among diabetics with metabolic syndrome than without metabolic syndrome. Conclusions: Quality of life with respect to physical, psychological and social domain among diabetics with metabolic syndrome was reduced significantly.